Molecular Control of Oligodendrocyte Development. Issue 4 (April 2019) - Elbaz, Benayahu; Popko, Brian
Abstract : Myelin is a multilayer lipid membrane structure that wraps and insulates axons, allowing for the efficient propagation of action potentials. During developmental myelination of the central nervous system (CNS), oligodendrocyte progenitor cells (OPCs) proliferate and migrate to their final destination, where they terminally differentiate into mature oligodendrocytes and myelinate axons. Lineage progression and terminal differentiation of oligodendrocyte lineage cells are under tight transcriptional and post-transcriptional control. The characterization of several recently identified regulatory factors that govern these processes, which are the focus of this review, has greatly increased our understanding of oligodendrocyte development and function. These insights are critical to facilitate efforts to enhance OPC differentiation in neurological disorders that disrupt CNS myelin. Highlights: The development of oligodendrocyte lineage cells is regulated by tight transcriptional, post-transcriptional, translational, and post-translational control. The transcription factor SRY-box 10 (SOX10) is a major facilitator of the transcriptional control of oligodendrocyte lineage cell differentiation. miRNAs are major determinants in the terminal differentiation of oligodendrocytes. Eukaryotic translation initiation factors have a role in the translational control of oligodendrocyte development. Post-translational modification of transcription factors has a fundamental role in the transcriptional control of oligodendrocyte development.